(untitled) (Research, Society and Development, 2025)
Cervical cancer is a significant public health issue, with primary healthcare playing a key role in early detection and prevention. The diagnostic moment is often marked by vulnerability, fear, and anxiety, making humanization and patient-centered care essential. Nursing plays a central role in this process by providing emotional support, attentive listening, and comprehensive care. This integrative review aimed to analyze nursing contributions to humanization and patient reception during the diagnosis of cervical cancer in primary healthcare. Studies published between 2020 and 2025 in Medical Literature Analysis and Retrieval System Online and Google scholar that addressed nursing practices related to humanization, reception, and patient-centered care were included. Results indicate that nursing interventions significantly reduce patient distress, strengthen trust, and improve adherence to clinical follow-up. In conclusion, integrating humanized care strategies in primary healthcare is essential to enhance oncology services and provide comprehensive care for women.